2016
DOI: 10.5574/jaroe.2016.2.4.179
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Experimental Study of A TLP Type Floating Wind Turbine with Spoke Platform

Abstract: As the demand for renewable energy has increased following the worldwide agreement to act against global climate change and disaster, large-scale floating offshore wind systems have become a more viable solution. However, the cost of the whole system is still too high for practical realization. To make the cost of a floating wind system be more economical, a new concept of tension leg platform (TLP) type ocean floating wind system has been developed. To verify the performance of a 5-MW TLP type ocean floating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In addition, when a large-scale offshore wind farm is constructed, the installation area of mooring lines is smaller than that of catenary mooring lines because they are installed vertically downward, causing less interference with nearby structures or maritime fishing activities. Therefore, various studies have been conducted worldwide on TLP-type offshore wind turbine platforms (Adam et al, 2014;Kim et al, 2016;Chung et al, 2021;Ren et al, 2022). A previous study reported that the TLP platforms are economical because their life-cycle cost (LCC) is relatively lower than that of Spar plftforms (Pantusa et al, 2020).…”
mentioning
confidence: 99%
“…In addition, when a large-scale offshore wind farm is constructed, the installation area of mooring lines is smaller than that of catenary mooring lines because they are installed vertically downward, causing less interference with nearby structures or maritime fishing activities. Therefore, various studies have been conducted worldwide on TLP-type offshore wind turbine platforms (Adam et al, 2014;Kim et al, 2016;Chung et al, 2021;Ren et al, 2022). A previous study reported that the TLP platforms are economical because their life-cycle cost (LCC) is relatively lower than that of Spar plftforms (Pantusa et al, 2020).…”
mentioning
confidence: 99%